(untitled) (The Research of Medical Science Review, 2024)
Background: Cancer is a disease whereby affected body cells grow uncontrollably and deprive normal body cells of nutrients and appropriate function. The world health organization (WHO) fact sheet for February 2017 named Cancer as one of the major causes for deaths around the globe with 8.8million deaths in 2015 resulting in 1 per every 6 deaths being cancer mediated. Objective: The present study was conducted on prevalence of Cancer male and female population of district Buner, during July 2022 to July 2023. Methods: A total of 650 Patients cases were interviewed through questionnaires. During the study different problems regarding cancer were studied like Spicy food, Cold drink, Aggressive, Mental disturbance, Brest cancer, Stomach Cancer, Biopsy, PCR, Hair fall, Fatigue, Fever, Surgery, Medicine, Lung Cancer, and Liver cancer. Results: We reported about a total cases of Cancer diseases in District Buner are 650. In these cases we investigated 114(17.53%) cases of Breast Cancer, 160(24.16%) cases of Lung Cancer, 85(13.07%) cases of Liver Cancer, 27(4.15%) cases of Prostate Cancer, 36(5.53%) cases of Stomach Cancer, 130(20%) cases of Blood Cancer, 23(3.53%) cases of Bone Cancer, and 75(11.53%) cases of Intestine Cancer all these cases are found in district Buner. Conclusion: During the study we report a total cases of Cancer patient’s 650 in which males are 344 and females are 306. The ratio of Cancer disease is higher in the peoples having age 40 to 60 years and lower in age 20 to 40 years. The most effected Tehsil are Gadaizi due to blasting, mining and Daggar. Cancer disease is rare in Tehsil Chagharzi and Tehsil Mandanr.